External carbon costs and internal carbon pricing. (October 2022) - Trinks, Arjan; Mulder, Machiel; Scholtens, Bert
Abstract: The use of internal carbon prices (ICPs) is a practice by which companies voluntarily attach a hypothetical cost to their carbon emissions to help prioritize low-carbon investment projects. We find that ICP use is driven by external carbon constraints and by firms' exposure to formal carbon pricing systems, next to various firm and society characteristics. The size of the gap between countries' actual and intended emissions alone, without a translation into stringent climate policies, does not play a role. These findings inform policymakers and investors about when and why firms account for future carbon constraints internally. A key societal risk is that corporate investments are not sufficiently directed at a future low-carbon economy. Stringent climate policies that provide predictable pathways appear to help firms mitigate the misalignment of their investments by using ICPs and thereby contribute to a less erratic and less expensive transition of the energy system. Highlights: We study how the use and the level of internal carbon prices relates to carbon constraints and cost uncertainty. We use exposure to pricing systems and the carbon emission reduction rate implied by policies to assess constraints. We find that climate policy stringency increases the likelihood of adopting internal carbon prices. Firms use internal carbon prices to bring forward low-carbon investments in anticipation of future costs. Stringent climate policies and explicit pricing systems provide pathways for investment in low-carbon technologies.